Correction: Danner et al. It More than Adds Up: Interaction of Antibiotic Mixing and Temperature. Life 2021, 11, 1435 - Marie-Claire Danner; Sharon Omonor Azams; Anne Robertson; Daniel Perkins; Volker Behrends; Julia Reiss (Life, 2022)
The Authors wish to make the following corrections to this paper [...]